Polymer cyclization for the emergence of hierarchical nanostructures - Chaojian Chen (Nature Portfolio, 2021)
Synthetic polymer nano-objects with well-defined hierarchical structures are important for a wide range of applications such as nanomaterial synthesis, catalysis, and therapeutics. Here the authors demonstrate the strategy of fabricating controlled hierarchical structures through self-assembly of folded synthetic polymers.